![if a = ( cosa sina)and b = ( sina. - cos a) then ab if a = ( cosa sina)and b = ( sina. - cos a) then ab](https://tex.z-dn.net/?f=if+a+%3D+%28+cosa++sina%29and+b+%3D+%28+sina.+-++cos+a%29+then+ab)
Answers
Answered by
0
Step-by-step explanation:
a= (cosAsinA) & b=(sinA-cosA)
a= (cosAsinA) & b=(sinA-cosA)then ab = cosAsin²A-cos²AsinA
sin²A-cos²A=1
therefore : cosA x 1 x sinA
= cosAsinA
Similar questions
English,
1 month ago
Social Sciences,
1 month ago
English,
1 month ago
English,
3 months ago
Computer Science,
3 months ago
Math,
11 months ago
Chemistry,
11 months ago